Respiration characteristics and its responses to hydrothermal seasonal changes in reconstructed soils - Na Lei (Nature Portfolio, 2021)
Abstract Seasonal changes in respiration and the components of four reconstructed soils (gravel + meteorite + lou; gravel + shale + lou; gravel + sand + lou; and gravel + soft rock + lou) in barren gravel land were monitored using the soil carbon flux measurement system. The results showed that (1) the monthly average respiration rate and the rates of the components in the four reconstructed soils were the highest in summer and lowest in winter. In winter, the monthly average respiration rates of the four reconstructed soils were not different (p > 0.05). In summer, the monthly average respiration rate of the sand or meteorite reconstructed soil was different from that of the other three (p < 0.05). (2) The heterotrophic and autotrophic respiration rates were different between the four reconstructed soils (p < 0.05). The contribution of heterotrophic respiration to total respiration in the four reconstructed soils was greater than that of autotrophic respiration throughout the year. In winter, autotrophic respiration accounts for the smallest proportion of total respiration. As the temperature rises, the proportion of autotrophic respiration to total respiration gradually increases and peaks in summer. In summer, the proportion of heterotrophic respiration in the total respiration is the smallest. With the decrease in temperature, the proportion of heterotrophic respiration in total respiration gradually increases and peaks in winter. (3) The maximum and minimum values of the monthly average respiration rate of the four reconstructed soils coincided with the months of maximum and minimum soil temperature. The soil volumetric water content changed with the amount of precipitation. The correlation between soil respiration and temperature was greater than that between soil respiration and volumetric water content. (4) The correlation in seasonal variation between respiration of the four remodelled soils and hydrothermal factors in the study area can be characterised by an exponential function and power-exponential function.